Ammonia production from biomass via a chemical looping–based hybrid system. (20th March 2021) - Weng, Qingyan; Toan, Sam; Ai, Rongshen; Sun, Zhao; Sun, Zhiqiang
Abstract: Ammonia is an indispensable raw material in the chemical industry. A hybrid biomass conversion to ammonia system (HBCAS) is developed by means of the chemical looping process with the assistance of solar energy and wind power. The system consists of six modules: i) biomass gasification, ii) oxy-syngas combustion, iii) chemical looping air separation (CLAS), iv) chemical looping ammonia production (CLAP), v) power generation, and vi) water electrolysis. A simulation was conducted for feasibility analysis and parameter optimization using ASPEN Plus, focusing on the development of a coordinated distribution network of energy and materials. Multi-generation of NH3, N2, and H2 was achieved using biomass cascading. The thermally neutral requirements of HBCAS and the effects of the operating conditions of each module on the selectivities (MnO2, AlN, and NH3 ), product concentrations, production rates, and reactant conversions were comprehensively considered. The results indicate that ammonia selectivity of 79.36%, production rate of 34.1 kmol/h, and concentration of 65.65 vol% can be obtained under typical conditions with 1 kg/s biomass input, confirming the feasibility of the HBCAS and providing guidance for its use. Graphical abstract: Image 1 Highlights: A novel hybrid system, HBCAS, is developed with multi-generation of NH3, N2, and O2 . Ammonia is produced from carbothermal reduction via a chemical looping scheme. Feasibility of HBCAS was verified with operating parameters optimization. Auto-thermal operation can be achieved with the assistance of solar and wind. NH3 selectivity of 79.26% and single-day system efficiency of 45.46% are obtained.